RELATIONSHIP OF SERU M VISFATIN LEVELS WI TH SERUM ELECTROLYTES, LIVER PROFILE, HEPATIC ENZ YMES AND ANTHROPOMETRIC PARAM ETERS IN PREGNANT WO MEN WITH PREECLAMPSIA AND ECL AMPSIA DURING 3RD TR IMESTER - Asmat Shaheen; Luqman, Muhammad Waqas; Sofia Iqbal; Nida Khan; Sadia Fatima; Rubina Nazli (Journal of Ayub Medical College Abbottabad, 2022)
Background: Eclampsia and preeclampsia are among the serious complications of gestation and threaten the lives of both mother and foetus. A protein called visfatin, one of these adipokines, is evaluated for its effects on serum electrolytes, lipid profile and hepatic enzymes in preeclamptic and eclamptic patients. Methods: A sum of 234 pregnant women were enrolled in this cross-sectional study and divided in to 2 main groups, i.e., Group A (eclamptic/preeclamptic) Group B (control) pregnant women respectively. Serum visfatin levels (ng/mL), serum electrolytes and liver enzymes were determined for every patient, using relative diagnostic kits. Anthropometric measurements were also noted. Results: A total of 234 women (cases; n=160, controls; n=74) with gestation age of ‰¥20 weeks participated in this study. Group A had 86 (36.75%) women with preeclampsia and 74 (31.62%) women with eclampsia whereas Group B had 74 (31.62%) normotensive pregnant women. A strong significantly positive association was recorded for systolic (R2=78.78; p-value <0.000) and diastolic blood pressure (BP) (R2=78.52; p-value <0.000). Similar result was obtained for serum sodium ions (R2=3.09; p-value <0.002) and chloride ions (R2=7.36; p-value <0.000). Alkaline phosphatases (ALP) (R2=63.47; p-value <0.000) had also shown a strong positive and statistically significant association with visfatin levels. Conclusion: Serum visfatin significantly decreased the sodium and chloride levels whereas the levels of potassium remained unaffected. A very strong and positive association of visfatin levels with levels of bilirubin and alkaline phosphatases was also observed (ALP) but it found no effect on aspartate transferases (AST).